The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/2317-1545v42221611
|View full text |Cite
|
Sign up to set email alerts
|

Vigor test of (strong) normal intact Amburana cearensis (Allemão) A.C. Smith seedlings

Abstract: The aim of this study was to adapt the vigor test methodology of (strong) normal intact seedlings of Amburana cearensis and evaluate efficiency in physiological classification of seed lots. The study was conducted in two stages: morphological characterization of seedlings and physiological analysis of seed lots. To do so, the following tests were carried out: (strong) normal seedlings, germination, emergence, first count, germination speed index, tetrazolium, length of strong normal seedlings, length and dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…Which probably influences the absorption time of the solution. Affirming the relevance and importance of vigor test adequacy for seeds, Medeiros et al (2020) observed in seeds of Amburana cearenses (Allemão) A.C. Smith, significant correlations in the quantification of vigor of normal seedlings when compared to vigor using the tetrazolium test.…”
Section: Assay 1 Tetrazolium Testmentioning
confidence: 79%
“…Which probably influences the absorption time of the solution. Affirming the relevance and importance of vigor test adequacy for seeds, Medeiros et al (2020) observed in seeds of Amburana cearenses (Allemão) A.C. Smith, significant correlations in the quantification of vigor of normal seedlings when compared to vigor using the tetrazolium test.…”
Section: Assay 1 Tetrazolium Testmentioning
confidence: 79%
“…Deve sempre ser procurado na literatura alguma pesquisa ou informação sobre as formas de análise neste teste, existem para muitas espécies protocolos prontos que podem ser usados para tal. Exemplos diversos podem ser citados, com protocolos para espécies anuais e perenes, alguns destes podem ser visualizados nos escritos de Belniaki et al (2020), Medeiros et al (2020) e Mercado et al (2020).…”
Section: Página| 24 6 Análises De Vigorunclassified
“…A avaliação pode ser referida em percentagem de sementes viáveis e não viáveis. Períodos de embebição e métodos de leitura podem ser visualizados com maior exatidão nos escritos de Prado et al (2019), e Krzyzanowski et al (2019) e Medeiros et al (2020).…”
Section: Página| 24 6 Análises De Vigorunclassified
“…Logo, para melhor analisar a proposição da análise de Person, levou-se em consideração como critérios de classificação de correlação, quando o coeficiente r indicasse haver correlação positiva ou negativa entre as variáveis testadas, segundo a metodologia descrita por Medeiros et al (2020). As análises foram realizadas no R.…”
Section: Tempos De Embebiçãounclassified